2016
DOI: 10.3389/fpsyg.2016.00242
|View full text |Cite
|
Sign up to set email alerts
|

Undetectable Changes in Image Resolution of Luminance-Contrast Gradients Affect Depth Perception

Abstract: A great number of studies have suggested a variety of ways to get depth information from two dimensional images such as binocular disparity, shape-from-shading, size gradient/foreshortening, aerial perspective, and so on. Are there any other new factors affecting depth perception? A recent psychophysical study has investigated the correlation between image resolution and depth sensation of Cylinder images (A rectangle contains gradual luminance-contrast changes.). It was reported that higher resolution images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
(40 reference statements)
0
13
1
Order By: Relevance
“…They found that 60cpd or higher is required as the resolution for visual realness. It is also shown that high resolution beyond the visual acuity acts as depth perception [3][4]. This is considered as a higher level of perception studied by previous resolution displays up to 4K.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…They found that 60cpd or higher is required as the resolution for visual realness. It is also shown that high resolution beyond the visual acuity acts as depth perception [3][4]. This is considered as a higher level of perception studied by previous resolution displays up to 4K.…”
Section: Introductionmentioning
confidence: 80%
“…In the preceding study [1], 60 cpd twice as many as 30 cpd shows that realness increases and further cpd is recognized as depth. However, the size of the display used in the study is small and compared only to actual objects, and depth perception is limited by the cylinder of the grey scale [3][4]. We tested the viewing angle using a high-resolution display that is identical to normal TV and verified its effect by using real images, not just graphic images.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations